Commercialization of User Data by Developers of Medicines-Related Apps: a Content Analysis - Grundy, Quinn (J Gen Intern Med, 2019)
BACKGROUND: Developers of medicines-related apps collect a variety of technical, health-related, and identifying user information to improve and tailor services. User data may also be used for promotional purposes. Apps, for example, may be used to skirt regulation of direct-to-consumer advertising of medicines. Researchers have documented routine and extensive sharing of user data with third parties for commercial purposes, but little is known about the ways that app developers or “first” parties employ user data. OBJECTIVE: We aimed to investigate the nature of user data collection and commercialization by developers of medicines-related apps. APPROACH: We conducted a content analysis of apps’ store descriptions, linked websites, policies, and sponsorship prospectuses for prominent medicines-related apps found in the USA, Canada, Australia, and UK Google Play stores in late 2017. Apps were included if they pertained to the prescribing, administration, or use of medicines, and were interactive. Two independent coders extracted data from documents using a structured, open-ended instrument. We performed open, inductive coding to identify the range of promotional strategies involving user data for commercial purposes and wrote descriptive memos to refine and detail these codes. KEY RESULTS: Ten of 24 apps primarily provided medication adherence services; 14 primarily provided medicines information. The majority (71%, 17/24) outlined at least one promotional strategy involving users’ data for commercial purposes which included personalized marketing of the developer’s related products and services, highly tailored advertising, third-party sponsorship of targeted content or messaging, and sale of aggregated customer insights to stakeholders. CONCLUSIONS: App developers may employ users’ data in a feedback loop to deliver highly targeted promotional messages from developers, and commercial sponsors, including the pharmaceutical industry. These practices call into question developers’ claims about the trustworthiness and independence of purportedly evidenced-based medicines information and may create a risk for mis- or overtreatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-019-05214-0) contains supplementary material, which is available to authorized users.